EFEKTIVITAS PROGRAM PERHUTANAN SOSIAL DAN REFORMA AGRARIA DI KAWASAN HUTAN KABUPATEN BLITAR - Trijanto, Mohammad; Nurbaedah, Nurbaedah (Universitas Islam Kadiri, 2024)
The Social Forestry Program in Blitar Regency has not been running in accordance with its utilization and management rights. The response from KPH Perum Perhutani and the Blitar Regency Government was still very low regarding issues of social forestry and Agrarian Reform, so that the two programs that were formed for the community were still not running effectively. The purpose of this study is the effectiveness and obstacles of the Social Forestry and Agrarian Reform programs in the Blitar Regency Forest Area. This study uses an empirical approach. Data collection technique used is interview. The results of the research show that: 1) With the existence of the social forestry program, the community gets legal protection, so that if other parties want to take over or take over, they have legal power over the land they are working on. For the people who have undergone this program, they are greatly helped by the existence of the social forestry program; 2) Agrarian reform is very appropriate for residents in forest areas. This is specifically for people who have lived there since the Dutch era, their ancestors also came from there. Their house has long been built in the neighborhood. So that the Agrarian Reform program really helps the community; 3) All problems and obstacles in the implementation of the Social Forestry and Agrarian Reform programs can be resolved quickly. This obstacle was caused by several parties missing information related to the Social Forestry program. All this time the forest was managed by Perum Perhutani but now it turns out that the community has been given management rights by forming a KTH (Forest Farmers Group), then submitting an application for a utilization permit to the Ministry of Environment and Forestry. What underlies many of the proposals so far is because farmers want to be the main subjects in forest management, besides that there are also reasons that while working on forestry land they often experience pressure and intimidation from the foreman and even the paramedics of Perum Perhutani.